Cassia alata (Linnaeus) Roxburgh for skin: natural remedies for atopic dermatitis in Asia and their pharmacological activities - Yon, Jessica-Ai-Lyn; Lee, Sue-Kei; Keng, Jing-Wen; Chow, Sek-Chuen; Liew, Kai-Bin; Teo, Swee-Sen; Shaik Mossadeq, Wan Mastura; Marriott, Philip J.; Akowuah, Gabriel Akyirem; Ming, Long Chiau; Goh, Bey Hing; Chew, Yik-Ling (MDPI, 2022)
Atopic dermatitis (AD) is an inflamed skin condition with relapsing pruritus and cutaneous physiological dysfunction. This skin disorder is widespread around the world and frequently affects infants, children and adults. Natural products with bioactive lead compounds are the source of natural medicines for complementary and alternative therapy in managing AD. Cassia alata has been used traditionally as a remedy for a variety of health issues. In Asian countries, it is used as an ethnomedicine to treat skin conditions such pityriasis versicolor, ringworm, scabies, shingles, urticaria and itching. According to previously published studies, the phytochemicals in C. alata may have a wide range of significant pharmacological effects. AD management is highlighted here, as this review explores the literature on the pharmacological effects of C. alata and its phytochemical content. Specifically, antibacterial, wound healing, anti-inflammatory and antioxidant effects are reviewed and discussed in relation to AD management.